Akses Lahan, Ekslusi, dan Konflik dalam Dinamika Perubahan Agraria di Kawasan Hutan di Desa Napal Putih, Kabupaten Tebo, Sumatra - Muhammad Reza Halomoan; Arya Hadi Dharmawan; Satyawan Sunito (Sodality: Jurnal Sosiologi Pedesaan, 2023)
Extraction activities in forest areas in Indonesia have led to drastic changes in the ecological balance of forest regions. The Indonesian government responded by implementing the concept of Industrial Plantation Forest (HTI), which was granted to the private sector to address the damage caused by forest extraction while utilizing unproductive forest land. However, this policy failed to consider the presence of communities that controlled and utilized land. This triggered agrarian conflicts because of differing claims over land. Using qualitative research methods, this paper explores the issue of agrarian conflict through a political ecological analysis within the theoretical framework of access and exclusion. Thus, it elucidates why forest area conflicts in Napal Putih occur, who the actors are involved in each contestation process, and how the relationships among actors take shape.